2002
DOI: 10.1161/hc0502.103330
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in the Antiarrhythmics Versus Implantable Defibrillators Trial

Abstract: RN; and the AVID InvestigatorsBackground-Implantable cardioverter defibrillator (ICD) use reduces mortality in patients with serious ventricular arrhythmias compared with antiarrhythmic drug (AAD) use. However, the relative impact of these therapies on self-perceived quality of life (QoL) is unknown. Methods and Results-Three self-administered instruments were used to measure generic and disease-specific QoL in Antiarrhythmics Versus Implantable Defibrillators trial participants. Generalized linear models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
2
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 572 publications
(141 citation statements)
references
References 31 publications
3
119
2
12
Order By: Relevance
“…With the advent and then dominance of primary prevention indications, avoidable shocks assumed a relatively larger proportion of total therapy [78][79][80][81][82][83]. Gradually, publications have increased awareness of the frequency and the diverse range of adverse outcomes associated with avoidable ICD therapy, and have demonstrated that avoidable ICD shocks can be reduced by evidence-based programming of the detection rate, detection duration, antitachycardia pacing (ATP), algorithms that discriminate supraventricular tachycardia (SVT) from VT, and specific programming to minimize the sensing of noise [81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Tachycardia Detection Programmingmentioning
confidence: 99%
“…With the advent and then dominance of primary prevention indications, avoidable shocks assumed a relatively larger proportion of total therapy [78][79][80][81][82][83]. Gradually, publications have increased awareness of the frequency and the diverse range of adverse outcomes associated with avoidable ICD therapy, and have demonstrated that avoidable ICD shocks can be reduced by evidence-based programming of the detection rate, detection duration, antitachycardia pacing (ATP), algorithms that discriminate supraventricular tachycardia (SVT) from VT, and specific programming to minimize the sensing of noise [81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Tachycardia Detection Programmingmentioning
confidence: 99%
“…Similar findings were recently reported from the Antiarrhythmics Versus Implantable Defibrillators (AVID) trial in which shock was again associated with worse physical and mental QOL. 23 The experience of shock may be confounded by the simultaneous negative appraisals of the ICD following shock. We have suggested that ICD shock may serve as a "sickness scoreboard" for patients, such that more shocks are perceived to equate to less health and initiate a cycle of negative beliefs and expectations.…”
Section: Psychological Adjustment and The Experience Of Shockmentioning
confidence: 99%
“…After one year follow-up, similar alterations in QoL were observed between both the ICD and antiarrhythmic groups; with adverse symptoms of therapy being associated with reduced QoL in both groups (mean age of 64 years). 77) An increased frequency of sporadic shocks was found to be associated with a reduced QoL in the ICD recipients. In a similar analysis of the Canadian Implantable Defibrillator Study (CIDS) in which patients (mean age 63 years) were randomized to ICD therapy or amiodarone, emotional and physical heath scores were shown to improve significantly in the ICD group but not the amiodarone randomized group.…”
Section: Quality Of Lifementioning
confidence: 98%